Impact of Project Based Learning Learning Model on the Ability of Deaf Children to Build the Structure of Sentence - Winda Greatta Zakiah (Indonesian Journal of Disability Studies, 2018)
Hearing impairment had impact to the students' speech ability. Students had hindrance to the communication process especially in sentence structure causing the sentence difficult to understand. The aim of this research is to examine the effect ofÂ  project based learning model on the sentence structure of children with hearing impairment. Design of this research is pre-experiment One Group Pretest-Posttets Design. Subjects of the research are 7 children with hearing impairment grade 5 at SLB B YRTRW Surakarta. The data collection techniques were objective and subjective written test, and oral test. The data analysis technique using non-parametric statistical analysis method, Wilcoxon Signed Rank Test with SPSS 22. The result shows that the average score in post-test 61.6 higher than the pretest 31.15. The result of this research was significant influence ofÂ  project based learning toward sentence structure of children with hearing impairment grade 5 in SLB B YRTRW Surakarta year 2017/2018.